Outcomes of Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia Comparing Prostate Size of more than 80 Grams to Prostate Size less than 80 Grams - Joshi, HN; de Jong, IJ; Karmacharya, RM; Shrestha, B; Shrestha, R (Kathmandu University Medical Journal, 2015)
Background Benign prostatic hyperplasia is a condition occurring in elderly men in which the prostate gland is enlarged, hence the condition also known as benign enlargement of prostate. Benign hyperplasia can lead to both obstructive and irritative symptoms. Transurethral resection of prostate (TURP) still remains the gold standard modality of surgical treatment of obstructive lower urinary tract symptoms due to Benign hyperplasia. Objectives The objective of this study was to evaluate the outcomes of TURP in large prostate (>80 grams) in comparison to small prostate (<80 grams) in terms of efficacy, safety and complications. Methods A total of 65 cases included in this prospective study, which were operated by a single surgeon with conventional monopolar TURP using standard technique. Intra -operative and post-operative complications, pre and post- operative quality of life (QoL) and international prostate symptom score (IPSS), operative time, time to removal of catheter and hospital stay were evaluated between small and large prostate gland volumes. Results Out of 65 cases, 30 were with large prostate size i.e. 80 grams or more (group 1), and 35 cases were with small prostate size than 80 grams size (group 2). Mean age was 71.8 SD ± 6.9 years in group 1 and 68.2 SD ± 12.7 years in group 2. The mean preoperative volume of prostate was 88.8 grams (range 80-115 grams) in group 1 and 40.3 (range 20-65 grams) in group 2. The mean preoperative post void residual volume of urine (PVRU) was 244 ml SD ± 190.8 ml in group 1 and 117 ml ± 70.3 ml in group 2. Mean resection time in group 1 was 110 (range 90-130) minutes and in group 2 it was 90 minutes (range 55-115) minutes. There were quite satisfactory improvements in IPSS and QoL. No significant complications were observed except TUR syndrome in 2 cases from group 2, which were managed well in postoperative period. Conclusion With meticulous resection and intra-operative haemostasis using continuous out flow resectoscope, conventional monopolar TURP is equally safe and effective in large size prostate as compare in small size. Kathmandu University Medical Journal Vol.12(3) 2014; 163-167